Integrated care for community dwelling older Australians. Issue 2 (14th February 2019) - Mann, Jennifer; Devine, Sue; McDermott, Robyn
Abstract : Purpose: Integrated care is gaining popularity in Australian public policy as an acceptable means to address the needs of the unwell aged. The purpose of this paper is to investigate contemporary models of integrated care for community dwelling older persons in Australia and discuss how public policy has been interpreted at the service delivery level to improve the quality of care for the older person. Design/methodology/approach: A scoping review was conducted for peer-reviewed and grey literature on integrated care for the older person in Australia. Publications from 2007 to present that described community-based enablement models were included. Findings: Care co-ordination is popular in assisting the older person to bridge the gap between existing, disparate health and social care services. The role of primary care is respected but communication with the general practitioner and introduction of new roles into an existing system is challenging. Older persons value the role of the care co-ordinator and while robust model evaluation is rare, there is evidence of integrated care reducing emergency department presentations and stabilising quality of life of participants. Technology is an underutilised facilitator of integration in Australia. Innovative funding solutions and a long-term commitment to health system redesign is required for integrated care to extend beyond care co-ordination. Originality/value: This scoping review summarises the contemporary evidence base for integrated care for the community dwelling older person in Australia and proposes the barriers and enablers for consideration of implementation of any such model within this health system.